On the Interpretation of Hysteresis Loop for Electronic and Ionic Currents in Organic Memristive Devices. Issue 18 (13th February 2020) - Battistoni, Silvia; Verna, Alessio; Marasso, Simone Luigi; Cocuzza, Matteo; Erokhin, Victor
Abstract : Being promising elements for neuromorphic computation, memristive devices have been often described as crucial elements for mimicking important synapse properties, such as memory and learning. Among them, organic memristive devices (OMDs) can claim low‐cost fabrication processes and the easy tunability of their electrical properties. Up to now, the major bottleneck for their larger uses in neuromorphic computation is low rate of the resistance switching and stability. Herein, a new approach is reported, based on the use of a liquid electrolyte, leading to the manufacturing of OMD with higher stability and faster resistive switching. Abstract : In organic memristive devices, the fast and stable resistive switching is due to variation of the oxidation state of the polymer (polyaniline) caused by the application of a specific voltage value.